2015
DOI: 10.2174/0929867322666150114151946
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transporters in Brain Tumors

Abstract: Ion transporters are important in regulation of ionic homeostasis, cell volume, and cellular signal transduction under physiological conditions. They have recently emerged as important players in cancer progression. In this review, we discussed two important ion transporter proteins, sodium-potassium-chloride cotransporter isoform 1 (NKCC-1) and sodium-hydrogen exchanger isoform 1 (NHE-1) in Glioblastoma multiforme (GBM) and other malignant tumors. NKCC-1 is a Na+-dependent Cl− transporter that mediates the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 127 publications
0
34
1
Order By: Relevance
“…Pharmacological inhibition of NHE1 has been shown to suppresses the G1/S and G2/M cell cycle phase by the reduction of cell cycle regulator expression, such as cyclin D1 and cyclin B1 [ 39 ]. NHE1 protein also stimulates the matrix metalloproteinases family and promote tumor invasion via ERK1/2 and p38 MAPK signaling pathways [ 42 ]. In our study, inhibition of NHE1 with HOE642 (0.5 mg/kg per day for continuous 5 days) significantly decreased the tumor volume and tumor invasion in mouse intracranial glioma animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of NHE1 has been shown to suppresses the G1/S and G2/M cell cycle phase by the reduction of cell cycle regulator expression, such as cyclin D1 and cyclin B1 [ 39 ]. NHE1 protein also stimulates the matrix metalloproteinases family and promote tumor invasion via ERK1/2 and p38 MAPK signaling pathways [ 42 ]. In our study, inhibition of NHE1 with HOE642 (0.5 mg/kg per day for continuous 5 days) significantly decreased the tumor volume and tumor invasion in mouse intracranial glioma animal model.…”
Section: Discussionmentioning
confidence: 99%
“…One reasonable explanation is that the GSC compartment has a diminished ability to manage cation exchange. Recently, several authors have found an association between Na + /K + exchange and stem/progenitor cell characteristics and also poor prognosis, such as, aggressive and resilient tumoral growth [ 36 , 37 ]. An implication of this hypothesis is that disruption of the balance of Na + and K + , as brought about by SLM, could be therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…Na/H exchanger isoform 1 (NHE1) plays an important role in the progression of GBM 16 . NHE1 ( SLC9A1 ) mRNA expression in GBM tumor tissues correlates with worse patient outcome in the Repository for Molecular Brain Neoplasia Data (REMBRANDT) 17 .…”
Section: Introductionmentioning
confidence: 99%